2014
DOI: 10.1038/nn.3778
|View full text |Cite
|
Sign up to set email alerts
|

Beyond genotype: serotonin transporter epigenetic modification predicts human brain function

Abstract: We examined epigenetic regulation in regards to behaviorally and clinically relevant human brain function. Specifically, we found that increased promoter methylation of the serotonin transporter gene predicted increased threat-related amygdala reactivity and decreased mRNA expression in postmortem amygdala tissue. These patterns were independent of functional genetic variation in the same region. Furthermore, the association with amygdala reactivity was replicated in a second cohort and was robust to both samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
113
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(136 citation statements)
references
References 29 publications
(41 reference statements)
18
113
0
1
Order By: Relevance
“…The authors provided evidence for the utility of threat-related amygdala reactivity using fMRI as a predictive biomarker of risk for psychological vulnerability to stressful life events. The results of this study are consistent with previous studies that identify risk factors for depression and anxiety disorders in relation to increased amygdala reactivity to threat [54][55][56]. More research is required to implicate any neurobiological mechanisms of PTSD risk or resilience; however, identifying biomarkers and neuroimaging models for the purposes of diagnosis of PTSD would shift the paradigm from relying solely on self reported symptoms and help determine targets for pharmacologic treatment.…”
Section: Neurobiological Factorssupporting
confidence: 86%
“…The authors provided evidence for the utility of threat-related amygdala reactivity using fMRI as a predictive biomarker of risk for psychological vulnerability to stressful life events. The results of this study are consistent with previous studies that identify risk factors for depression and anxiety disorders in relation to increased amygdala reactivity to threat [54][55][56]. More research is required to implicate any neurobiological mechanisms of PTSD risk or resilience; however, identifying biomarkers and neuroimaging models for the purposes of diagnosis of PTSD would shift the paradigm from relying solely on self reported symptoms and help determine targets for pharmacologic treatment.…”
Section: Neurobiological Factorssupporting
confidence: 86%
“…The amygdala has also received widespread attention due to its involvement in emotion processing and response to aversive cues. Threat-related amygdala reactivity was associated with SLC6A4 methylation in two independent cohorts, including one in a longitudinal study where the increase in methylation after a 2 to 3 years of follow-up correlated to an increase in threat-related amygdala reactivity in the same time period (Nikolova et al, 2014;Swartz et al, 2016). Moreover, Muehlhan et al found the connectivity between the amygdala and key nodes of the salience network to be associated with SLC6A4 methylation (Muehlhan et al, 2015).…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…In addition, a number of studies have tried to correlate peripheral epigenetic changes with brain function using neuroimaging approaches. For example, increased promoter methylation of the serotonin transporter gene in peripheral blood predicted increased threat-related amygdala reactivity, and increased methylation of the same sites predicted decreased mRNA expression in post-mortem amygdala tissue (Nikolova et al, 2014). To date, however, the mechanistic insights from studies correlating peripheral epigenetic changes with brain imaging are limited.…”
Section: Epigenetic Modifications As a Potential Target Of Psychiatrimentioning
confidence: 99%